Financial accounting : information for decisions - Wild, John J. (Dubuque, IA : McGraw Hill LLC, 2024)
"Learning science reveals that students better learn and retain information when text is presented in a direct, concise, and systematic manner within a blocked format. Our new edition delivers the content you expect in fewer pages. Visual aids and numerous demonstration and Hint (guided example) videos offer additional learning aids. New summary Cheat Sheets conclude each chapter to visually reinforce key concepts and procedures, and they offer a link for students as they search for answers"--
Includes index.
Ages 18+
Grades 10-12
Keywords: Accounting